Burden of Care and Social Behaviour Problem of Patients with Schizophrenia - Othman, Zahiruddin; Salleh, Mohd Razali (Japan International Cultural Exchange Foundation, 2008)
Objective: To assess the relationship between levels of burden on primary caregivers and social behaviour problem of patients with schizophrenia. Design : Cross-sectional study. Materials and Methods.' The study involved forty five patients attending Psychiatry Clinic. The level of burden on primary caregivers was assessedu sing Burden on Family Interview Sineaute (BFS) and the social behaviour problem of patients with schizophrenia was assessedu sing Social Behaviour Schedule (SBS). Results: Employment status and monthly household income of primary caregivers were significantiy correlated with amount of burden. Caregivers experienced enormous amount of botl subjective ana onlective burden. Financial burden was the greatest objective burden affecting at least one third of the caregivelrs. Amount of burden experienced by primary caregivers was significantly correlated with social behaviiur problem of patients particularly hostility, over activity, restlessness, and destructive behaviour. Conclusion: The levels of burden on caregivers are high with employment status and monthly household income of caregivers are predictive of higher levels of burden.